Flood Detection and Prevention System - Ahmad, Mohamad Luqman; Suhaimi, Suhazlan (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Flood is the most damaging natural disaster that happens everywhere in the world. The government would spend billions of ringgits to tackle it by creating public info flood website. The website could only be accessed by the user with an internet connection. To tackle this the researcher, develop a Flood Detection and Prevention System to sends a flood SMS alert directly to the user without the use of an internet connection. FDAP hardware consists of one microcontroller to process input and output, three sensors to detect rain, water level, and temperatures, and One GSM module to send SMS to the user directly to their phone. Development of the system will use Rapid Prototyping that focused on creating multiple prototypes until a finished product is developed. The product then will be analyzed for its usage on flood detection and prevention of flooding. A fully functional system will be developed including an SMS feature and a Web Server. Test involved functionality and acceptance test which uses a simulation environment that is created using a physical model and replica of flood phenomenon. FDAP system developed will be useful to rural villages to detect flood earlier and prevent it from harming live or properties. The finding of this study is expected to gain informative data for future flood analysis and study.